Endocytic Regulation of Voltage-Dependent Potassium Channels in the Heart - Kuniaki Ishii; Ikuo Norota; Yutaro Obara (Elsevier, 2012)
Understanding the regulation of cardiac ion channels is critical for the prevention of arrhythmia caused by abnormal excitability. Ion channels can be regulated by a change in function (qualitative) and a change in number (quantitative). Functional changes have been extensively investigated for many ion channels including cardiac voltage-dependent potassium channels. By contrast, the regulation of ion channel numbers has not been widely examined, particularly with respect to acute modulation of ion channels. This article briefly summarizes stimulus-induced endocytic regulation of major voltage-dependent potassium channels in the heart. The stimuli known to cause their endocytosis include receptor activation, drugs, and low extracellular [K+], following which the potassium channels undergo either clathrin-mediated or caveolin-mediated endocytosis. Receptor-mediated endocytic regulation has been demonstrated for Kv1.2, Kv1.5, KCNQ1 (Kv7.1), and Kv4.3, while drug-induced endocytosis has been demonstrated for Kv1.5 and hERG. Low [K+]o-induced endocytosis might be unique for hERG channels, whose electrophysiological characteristics are known to be under strong influence of [K+]o. Although the precise mechanisms have not been elucidated, it is obvious that major cardiac voltage-dependent potassium channels are modulated by endocytosis, which leads to changes in cardiac excitability. Keywords:: endocytosis, voltage-dependent potassium channel, cardiac excitability, clathrin, caveolin